Genotypes of NK cell KIR Receptors, Their Ligands, and Fcγ Receptors in the Response of Neuroblastoma Patients to Hu14.18-IL2 Immunotherapy: A Children’s Oncology Group Report - Delgado, DC (2010)
Response to immunocytokine (IC) therapy is dependent on natural killer (NK) cells in murine neuroblastoma (NBL) models. Furthermore, killer immunoglobulin-like receptor (KIR) / KIR-ligand mismatch is associated with improved outcome to autologous stem cell transplant for NBL. Additionally, clinical anti-tumor response to monoclonal antibodies has been associated with specific polymorphic-FcγR alleles. Relapsed/refractory NBL patients received the hu14.18-IL2 IC (humanized anti-GD2 monoclonal antibody linked to human IL2) in a Children’s Oncology Group (COG) Phase II trial. In this report, these patients were genotyped for KIR, HLA and FcR alleles to determine if KIR receptor-ligand mismatch or specific FcγR alleles were associated with anti-tumor response. Thirty-eight of 39 patients enrolled had DNA available for analysis; 24 were found to have autologous KIR/KIR -ligand mismatch; 14 were matched. Seven of 24 mismatched patients experienced either complete response or improvement of their disease after IC therapy. There was no response or comparable improvement of disease in patients who were matched. Thus KIR/KIR-ligand mismatch was associated with response/improvement to IC (p = 0.03). There was a trend towards patients with the FcγR2A 131-H/H genotype showing a higher response rate compared to other FcγR2A genotypes (p = 0.06). These analyses indicate that response or improvement of relapsed/refractory neuroblastoma patients after IC treatment is associated with autologous KIR/KIR-ligand mismatch, consistent with a role for NK cells in this clinical response.